A maladjustment and power conceptualisation of diversity in organisations: implications for cultural stigmatisation and expatriate effectiveness. (1st January 2011) - Martinez, Arthur D.; Ferris, Gerald R.; Segrest, Sharon L.; Buckley, M. Ronald
Belonging to a group that is in the minority in an organisation (e.g., racial, cultural) inherently puts individuals at a social disadvantage among the majority group, which can position them in ways so as not to be able to build political skill and acquire power and influence in organisations. Those in the minority must feel genuinely committed to their groups while simultaneously leveraging opportunities outside their groups, if they are to secure and maintain personal power. The propositions provided in this conceptualisation argue that individuals who are less committed to their group tend to be significantly more personally maladjusted, which, in turn, reduces the degree of political skill they develop and undermine their personal power levels and effectiveness.